Assessment of Functional Policentricity in the Romanian County Residence Municipalities - ANTONIO TACHE (Romanian Review of Regional Studies, 2016)
In 2002, John Friedmann concluded that “Almost everyone will coexist in a single global urban network, which will operate on the basis of global competition.” These challenges were mentioned in the EU 2020 Strategy (EC, 2010), where European policy is focused on competitive and inclusive metropolitan development. One of the main problems that emerge when adopting functional urban areas (or metropolitan areas) as territorial units of analysis and policy development in European countries is the lack of generally accepted standards for their identification. This problem prevents comparative research between European countries using functional urban areas or metropolitan areas as territorial units of analysis. This article presents an original methodology for assessing the functional policentricity of county seat in Romania, based on ESPON 1.1.1. programme criteria, particularly the classification of various categories of cities in the European Union.